Zuo Jin Wan Reverses the Resistance of Colorectal Cancer to Oxaliplatin by Regulating the MALAT1/miR-200s/JNK Signaling Pathway. (7th October 2022) - Wei, Zhenzhen; Zhou, Jing; Yu, Hao; Pu, Yunzhou; Cheng, Yuelei; Zhang, Yi; Ji, Qing; Zhu, Huirong
Abstract : Background . Oxaliplatin (L-OHP) is a common chemotherapy drug used in the treatment of colorectal cancer (CRC). Our previous work showed that Zuo Jin Wan (ZJW), a traditional Chinese medicine prescription, could improve sensitivity to L-OHP in the treatment of CRC, but the detailed mechanism is not clear. In previous mechanistic studies, we found that the miR-200s expression in CRC is associated with L-OHP sensitivity through regulation of MDR1/p-gp and the downstream c-JunN-terminal kinase (JNK) signaling pathway. Moreover, lncRNA-MALAT1 offers great potential in the regulation of drug resistance by interacting with miR-200s. Therefore, in this work, we explored whether ZJW could reverse L-OHP resistance in CRC by regulating MALAT1, miR-200s, and the downstream signaling pathway. Methods . Cell Counting Kit-8 and flow cytometry were used to detect the effects of ZJW combined with L-OHP on chemotherapy tolerance and cell apoptosis of HCT116/L-OHP cells. Western blotting and quantitative real-time PCR (qRT-PCR) were used to detect the activation of the JNK signaling pathway and the protein and mRNA expression levels of the drug resistance-related MDR1/ABCB1 gene in HCT116/L-OHP cells treated with ZJW. The binding sites of MALAT1 and miR-200s were predicted by bioinformatics tools and confirmed by qRT-PCR. qRT-PCR was used to detect the expression of miR-200s and MALAT1 in HCT116/L-OHP cells treated with ZJW. A xenograft model of CRC in nude mice was established to observe the effect of ZJW combined with L-OHP on the growth of subcutaneously transplanted tumors. Apoptosis in tumor cells was detected by TUNEL staining. The activation of the JNK signaling pathway and the expression of drug resistance-related proteins were detected by immunohistochemistry and immunofluorescence. qRT-PCR was used to detect the expression of miR-200s and the MALAT1 gene in the tumors. Results . Our study showed that ZJW could significantly decrease the proliferation and promote apoptosis of HCT116/L-OHP cells treated with L-OHP. We further proved that ZJW could reverse the drug resistance of HCT116/L-OHP cells by reducing MALAT1, indirectly upregulating miR-200s, alleviating the activation of the JNK signaling axis, and downregulating the expression of resistance proteins such as MDR1/ABCB1 and ABCG2. ZJW combined with L-OHP inhibited the growth of subcutaneously transplanted tumors and induced apoptosis in nude mice. ZJW reduced the expression of MALAT1 and upregulated the expression of miR-200s in transplanted tumors. In addition, ZJW also alleviated the activation of the JNK signaling pathway while reducing the expression of MDR1/ABCB1 and ABCG2. Conclusions . Our study identified that MALAT1 promotes colorectal cancer resistance to oxaliplatin by reducing the miR-200s expression. ZJW may reverse chemoresistance by inhibiting the expression of MALAT1 and regulating the miR-200s/JNK pathway, providing an experimental basis for the clinical application of ZJW in relieving chemotherapy resistance.